Design of Biogas Reactor as a Sustainable Energy Source in Pauh Sub-District Padang, West Sumatra - Ramli Ramli; Letmi Dwiridal (Fakultas MIPA Universitas Negeri Padang, 2018)
Cow dung waste in Pauh sub-district is widely available. Only partly used as a traditional fertilizer. In fact, the utilization of cow dung is one of the alternative sources of renewable energy. Although biogas technology is not something new in Indonesia, the obstacles faced by farmers are their lack of knowledge about processing cow dung into biogas and making of biogas reactors. Community service has been undertaken to provide knowledge through guidance and counseling methods to farmers about biogas, biogas reactor manufacturing and technology, and the advantages of biogas reactors, both in terms of economic and environmental values. Stages of the implementation of the activities; 1). Provide guidance and counseling to farmers about biogas and how to manufacture biogas reactor, 2). Provide guidance and counseling about the safety of biogas reactors, 3). Conduct periodic monitoring of farmer groups that are partners to the continuity and continuity of activities. The result of the activity is the availability of biogas reactor in farmer group in Pauh sub-district. The fermentation process to produce biogas in the reactor is approximately 3 weeks. Biogas reactors are built easy to make and cheap.